A complete chloroplast genome of Keteleeria davidiana (Pinaceae) and its phylogenetic implications. Issue 7 (3rd July 2021) - Zhang, Min; Li, Yuan-Yuan; Chai, Zi-Han; Zhu, Yue; Duan, Yi-Fan
Abstract: Keteleeria davidiana (Bertrand) Beissner 1891 (Pinaceae) is a rare tertiary relict plant endemic to China. However, since the main morphological characteristics used for identifying K. davidiana are variable, some taxonomic treatments within the species are still controversial. Here a complete chloroplast genome of K. davidiana representing a special genotype was assembled, which could provide more information for the taxonomic study of this species. The assembled genome was 117, 642 bp in length with a large single-copy (LSC) region (74, 825 bp), a small single-copy (SSC) region (40, 247 bp), and two incomplete inverted repeats (IRs) regions (1285 bp each). In total, 118 genes were predicted, including 4 rRNA s, 34 tRNA s, and 80 protein-coding genes. The overall GC content of the assembled genome was 38.5%. Phylogenetic analysis showed that different accessions of K. davidiana formed a clade with relatively low support (bootstrap value = 71), which indicated a high level of sequences variation within the species.